Financial Professionals' Overconfidence: Is It Experience, Function, or Attitude?. (13th December 2011) - Gloede, Oliver; Menkhoff, Lukas
Abstract This paper examines financial professionals' overconfidence in their forecasting performance. We compare individuals' self‐rating of performance with the true performance, both measured relative to the same peer group. The forecasters in our sample show overconfidence on average, although to a moderate degree, including many cases of underconfidence. In analysing this, we find that working experience is accompanied by less overconfidence. Function is also related to less overconfidence, such as being a fund manager and using fundamental analysis. The same effect is found for the attitude to herd, whereas recent success appears with more overconfident professionals.